2021
DOI: 10.1016/j.kint.2021.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Kidney disorders as serious adverse drug reactions of remdesivir in coronavirus disease 2019: a retrospective case–noncase study

Abstract: protecting immune-compromised patients. In the presence of scarce resources, equitable and effective risk-benefit allocation will be vital, prioritizing vulnerable patients. Timing immunotherapy with vaccination and determining vaccination response will be crucial. Concurrent SARS-CoV-2 infection should not prevent delivery of effective immunomodulatory therapy in patients with severe autoimmune diseases, essential for the protection and recovery of vital organ function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 4 publications
1
24
0
1
Order By: Relevance
“…The use of Remedesivir led to deranged kidney and liver functions. A similar causal association between Remedesivir and kidney disorders has also been reported byChouchana et al (2021) [16]. Majority of ADRs in this study presented as rash and urticaria.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The use of Remedesivir led to deranged kidney and liver functions. A similar causal association between Remedesivir and kidney disorders has also been reported byChouchana et al (2021) [16]. Majority of ADRs in this study presented as rash and urticaria.…”
supporting
confidence: 90%
“…With the evolving knowledge on the pathophysiology of the disease, drug regimens are constantly being updated and modi ed, adding more numbers to the existing list of drugs being used, especially in severe cases.Hydroxychloroquine, Ivermectin, Doxycycline, Favipiravir and multivitamins were recommended for treatment of mild (to moderate) category COVID patients. Convalescent Plasma therapy, anti-in ammatory drugs (such as methylprednisolone or dexamethasone), antivirals, immunomodulators, anticoagulants (UFH or LMWH), thiamine, vitamin C and antimicrobials and or antifungals as per local antibiotic policy were recommended for COVID-19 patients who progressed to the in ammatory phase (moderate/ severe category) of the disease [1]. While the occurrence of adverse drug reactions (ADRs) in COVID 19 patients has not been extensively studied, ndings from retrospective trials in non-COVID cases indicate that it is likely to be high [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Two analyses of the World Health Organization pharmacovigilance database have identified that reports of AKI are more commonly reported after remdesivir use compared to other medications used to treated COVID-19 (hydroxycholoroquine, dexamethasone, tocilizumab) [31,32]; however reporting bias exists in pharmacovigilance databases.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide analogue prodrug remdesivir was granted emergency use authorization (EUA) for the treatment of COVID-19 in May 2020 for its ability to inhibit viral RNA-dependent RNA polymerase (59). While studies have shown that remdesivir treatment in AKI and CKD patients is tolerated well, the active metabolite of remdesivir is eliminated by the kidneys and has been reported to increase chances of developing AKI in remdesivir-treated patients (60)(61)(62). To investigate the efficacy of remdesivir, we infected kidney organoids with SARS-CoV-2 (WA1) or SARS-CoV-2-mNG, and then treated the infected organoids with a 2 µM dose of remdesivir immediately after infection (Figure 6A).…”
Section: Therapeutics Reduce Sars-cov-2 Infection and Replication In Kidney Organoidsmentioning
confidence: 99%